ON THE DYNAMICS OF A DOUBLE CLUSTER SYSTEM AND THE CLUSTERS H AND X PERSEI - PISMIS, P (UNAM, Observatorio Astronómico Nacional, CD MEXICO, DF, MEX, 1958)
In the present investigation we attempt to determine whether h and X Persei are physically related. An attempt in this direction is made by examining the dynamical consequences of the proximity of the two clusters. We find that the real distance between t
BOL OBS TONAN TACUB
Keywords: DYNAMICS, DOUBLE CLUSTER, SYSTEM, CLUSTERS, H, X, PERSEI; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS